Identification of nucleotides in E. coli 16S rRNA essential for ribosome subunit association - Pulk, Arto (Cold Spring Harbor Laboratory Press, 2006)
The ribosome consists of two unequal subunits, which associate via numerous intersubunit contacts. Medium-resolution structural studies have led to grouping of the intersubunit contacts into 12 directly visualizable intersubunit bridges. Most of the intersubunit interactions involve RNA. We have used an RNA modification interference approach to determine Escherichia coli 16S rRNA positions that are essential for the association of functionally active 70S ribosomes. Modification of the N1 position of A702, A1418, and A1483 with DMS, and of the N3 position of U793, U1414, and U1495 with CMCT in 30S subunits strongly interferes with 70S ribosome formation. Five of these positions localize into previously recognized intersubunit bridges, namely, B2a (U1495), B2b (U793), B3 (A1483), B5 (A1418), and B7a (A702). The remaining position displaying interference, U1414, forms a base pair with G1486, which is a part of bridge B3. We contend that these five intersubunit bridges are essential for reassociation of the 70S ribosome, thus forming the functional core of the intersubunit contacts.